Alimentacion de cerdos con raciones basadas en yuca - Maner, JH (International Center for Tropical Agriculture, 1971)
Three methods of feeding growing and finishing pigs fresh cassava and protein supplement are described: (1) supplement and cassava ad libitum; (2) cassava ad libitum and the supplement in controlled quantities to satisfy the daily requirements of protein in pigs depending on their wt.; and (3) a balanced mixture of fresh cassava and supplement prepared to supply a certain protein level, ad libitum. (AS)